The Factors in the Emergence of Smallholder Rubber Plantation in Tapanuli: 1906 - 1942 - Edi Sumarno; Ginting, Junita Setiana; Karina, Nina; Lubis, M. Azis Rizky (International Journal of Culture and Art Studies, 2019)
Latex has become more useful ever since the discovery of vulcanization methods, for it is used for the automotive industry and the manufacturing of electrical appliances. This then makes the price of latex soar as a result of high market demand for this white sticky thick ‘liquid’. Thus, it makes people interested in investing in rubber plants because they are considered to have a significant economic impact. Apart from the economic factors offered, there are other factors that are no less important, namely land, capital, laborer, and the existence of a market place for trade. These factors should be the main factors. Because, if these factors do not hold, the people in Tapanuli will still not be able to enjoy it however high the price of rubber is.